Asile et abus. Asyl und Missbrauch Regards pluridisciplinaires sur un discours dominant. Multidisziplinäre Perspektiven auf einen vorherrschenden Diskurs - Leyvraz, Anne-Cécile; Rey, Raphaël; Rosset, Damian; Stünzi, Robin (Social Cohesion and Cultural Pluralism, 2020)
The issue of asylum has polarised Swiss public opinion for the last four decades. Since its entry into force in 1981, the Asylum Law has been revised on numerous occasions, following a general trend toward more restrictiveness. Among the many discourses that have accompanied the politicisation of asylum, the rhetoric of the "fight against abuse" has emerged as a dominant framework of public debate, gathering a broad consensus. With few exceptions, existing scholarship on the Swiss context has remained silent on the issue. This collective and multidisciplinary book fills this gap in the literature by exploring the various forms and expressions of the discourse of abuse, as well as its impact on the production and implementation of asylum law.